2018
DOI: 10.3389/fpsyt.2018.00130
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion Shows Different Effects on Brain Functional Connectivity in Patients With Internet-Based Gambling Disorder and Internet Gaming Disorder

Abstract: IntroductionInternet gaming disorder (IGD) and gambling disorder (GD) share similar clinical characteristics but show different brain functional connectivity patterns. Bupropion is known to be effective for the treatment of patients with IGD and GD. We hypothesized that bupropion may be effective for the treatment of Internet-based gambling disorder (ibGD) and IGD and that the connections between the default mode network (DMN) and cognitive control network (CCN) would be different between ibGD and IGD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
0
35
0
1
Order By: Relevance
“…In relation to therapeutic approaches to IGD, several studies investigated the potential utility of different psychopharmacological agents, but, currently, no medication has been approved for this condition [ 24 , 46 ]. As far as antidepressants are concerned, the administration of Bupropion has shown a reduction of average time spent online and craving dimension in open-label [ 47 , 48 ] and randomized controlled studies [ 49 ]. Two open trials comparing the effectiveness of Bupropion and Escitalopram showed that both antidepressants were effective in reducing IGD symptoms, though Bupropion was more effective in improving attention and in impulsivity decrease [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to therapeutic approaches to IGD, several studies investigated the potential utility of different psychopharmacological agents, but, currently, no medication has been approved for this condition [ 24 , 46 ]. As far as antidepressants are concerned, the administration of Bupropion has shown a reduction of average time spent online and craving dimension in open-label [ 47 , 48 ] and randomized controlled studies [ 49 ]. Two open trials comparing the effectiveness of Bupropion and Escitalopram showed that both antidepressants were effective in reducing IGD symptoms, though Bupropion was more effective in improving attention and in impulsivity decrease [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific evidence on the utility of pharmacological therapy in OGD is scarce. Of note, a 12-week open-label study on 14 patients treated with Bupropion up to 300 mg/day highlighted a significant improvement of clinical symptoms [ 47 ]. In terms of psychotherapeutic interventions, a recent study demonstrated that Internet based CBT could improve access to treatment among non-help -seeking online gamblers [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bupropion was the most studied drug for IGD. Although there were concerns such as small sample size and short duration, two RCTs 38,40 and three additional studies 37,39,41 reported the efficacy of bupropion consistently. The efficacy of MPH and ATM treatment was also identified in two studies; 47,48 however, their effects have not been compared to those of a place- 37,41 combining functional neuroimaging showed that bupropion attenuated RSFC within the DMN and the SN and the neural response of the DLPFC to gaming cues.…”
Section: Discussionmentioning
confidence: 99%
“…В недавно проведенном исследовании корейских ученых [32] была подтверждена эффективность бупропиона в плане снижения выраженности проявлений ИА у пациентов с ИИР и интернет-гемблингом, а также депрессии, нарушений внимания и импульсивности. Вместе с тем авторы отметили различную фармакодинамику препарата у пациентов этих двух групп по данным фМРТ.…”
Section: фармакологическое лечениеunclassified